1636 Prevalence of mutations in parkin, PINK1, DJ-1 and LRRK2 in early onset Parkinson's Disease: a UK based study and systematic review. Issue 3 (9th February 2012) - Morris, H; Pearson, J P; Kilarski, L L; Wickremaratchi, M M; Knipe, M D W; Newsway, V; Williams, N M; Ben-Shlomo, Y; ,
Abstract : In approximately 3.6% of patients with Parkinson's disease symptoms start before the age of 45 (early onset Parkinson's disease—EOPD). EOPD patients have a high familial recurrence risk and there are three main autosomal recessive EOPD genes. Our aim was to establish the prevalence of mutations in these genes in a UK cohort and across previous studies. Cases were recruited locally, regionally and nationally. We screened 136 UK cases with EOPD for pathogenic mutations in Parkin, PINK1, DJ-1 and exon 41 of LRRK2. We have carried out a systematic review of previous studies looking at the frequency of pathogenic mutations in different patient groups. We identified five pathogenic mutations in Parkin, one in PINK1 and one in LRRK2. The rate of mutations overall was 5.1%. Mutations were found more commonly in patients with age at onset <40 (9.5%), an affected 1st degree relative (6.9%), an affected sibling (28.6%), or a consanguineous family history (50%). In our study EOPD mutation carriers were more likely to present with rigidity and dystonia and 6/7 mutation carriers had lower limb symptoms at onset. In our review of over 5500 EOPD cases reported in this study and previously, the proportion with Parkin, PINK1 and DJ-1 mutations were 8.64%, 3.73% and 0.44% respectively. PINK1 mutations occur more commonly in Asian subjects and are more likely to be homozygous. The overall frequency of mutations in known EOPD genes in the UK cohort is low. Our results show an increase in the likelihood of carrying mutations in patients with lower AAO, a positive family history and consanguinity.